Decontaminating N95 and SN95 masks with ultraviolet germicidal irradiation does not impair mask efficacy and safety. Issue 1 (September 2020) - O'Hearn, K.; Gertsman, S.; Sampson, M.; Webster, R.; Tsampalieros, A.; Ng, R.; Gibson, J.; Lobos, A.T.; Acharya, N.; Agarwal, A.; Boggs, S.; Chamberlain, G.; et al.
Summary: Inadequate supply of filtering facepiece respirators (FFRs) for healthcare workers during a pandemic such as the novel coronavirus outbreak (SARS-CoV-2) is a serious public health issue. The aim of this study was to synthesize existing data on the effectiveness of ultraviolet germicidal irradiation (UVGI) for N95 FFR decontamination. A systematic review (PROSPERO CRD42020176156) was conducted on UVGI in N95 FFRs using Embase, Medline, Global Health, Google Scholar, WHO feed, and MedRxiv. Two reviewers independently determined eligibility and extracted predefined variables. Original research reporting on function, decontamination, or mask fit following UVGI were included. Thirteen studies were identified, comprising 54 UVGI intervention arms and 58 N95 models. FFRs consistently maintained certification standards following UVGI. Aerosol penetration averaged 1.19% (0.70–2.48%) and 1.14% (0.57–2.63%) for control and UVGI arms, respectively. Airflow resistance for the control arms averaged 9.79 mm H2 O (7.97–11.70 mm H2 O) vs 9.85 mm H2 O (8.33–11.44 mm H2 O) for UVGI arms. UVGI protocols employing a cumulative dose >20, 000 J/m 2 resulted in a 2-log reduction in viral load. A >3-log reduction was observed in seven UVGI arms using >40, 000 J/m 2 . Impact of UVGI on fit was evaluated in two studies (16, 200; 32, 400 J/m 2 ) and no evidence of compromise was found. Our findings suggest that further work in this area (or translation to a clinical setting) should use a cumulative UV-C dose of 40, 000 J/m 2 or greater, and confirm appropriate mask fit following decontamination.